Bimbingan Belajar untuk Mengatasi Kesulitan Siswa Mempelajari Matematika Materi SPLDV - Anik Marliana Ningsih; Allifi Ilma Zakaria; Shofia Hidayah (FKIP Universitas Majalengka, 2026)
This community service activity aims to help students overcome difficulties in learning mathematics, particularly in the topic of Systems of Linear Equations in Two Variables (SPLDV). Based on initial observations at MTs Nurul Jadid, it was found that many ninth-grade students in Class IX Reguler 4 experienced difficulties in constructing mathematical models and solving problems using graphical, substitution, elimination, or combined methods. To address this issue, the learning sessions were carried out using interactive and contextual approaches that emphasize active student participation in the learning process. The activity was implemented in five stages: (1) planning and preparation, (2) pretest to measure students’ initial abilities, (3) guided learning sessions, (4) posttest to measure improvements in learning outcomes, and (5) evaluation. The program was conducted over four meetings, each lasting 40 minutes, involving 24 students from Class IX Reguler 4. The results indicated a significant improvement in learning outcomes. The average pretest score of 77.5 increased to 92.1 in the posttest. Students also demonstrated high enthusiasm and participation throughout the sessions. They reported feeling more confident and motivated in learning mathematics. Based on these results, it can be concluded that guided learning activities are effective in improving students’ understanding of Systems of Linear Equations in Two Variables (SPLDV) and in helping them overcome difficulties in learning mathematics. This program is expected to be continued and further developed to support the improvement of mathematics learning quality in the pesantren environment.